La cultura organizacional y su impacto en el desempeño laboral: revisión aplicada - Aliaga Sanez, Isabel Milagros (2023)
According to recent research, if a company has a solid culture, it will be able to align the behavior and/or conduct of its employees to improve their performance and, therefore, achieve the objectives set by the organization. Organizations should be interested in this because if employees have a culture of transparency and clear expectations, they will be able to face changes in the labor market and be more efficient. The aim of this study is to determine the impact of organizational culture on job performance. To this end, the recommendations of the PRISMA statement (Page et al., 2020) were applied and a search was conducted in the EBSCOhost, Proquest, APA Psycnet and Dialnet databases, and those investigations that fulfilled the inclusion and exclusion criteria were selected for analysis (n=10). It was evidenced that organizational culture has a significant and positive impact on job performance. Therefore, if workers' behaviors are aligned with the company's culture, their performance will increase. In contrast, if the culture is weak, their performance will be affected to the fullest